NAFLD is related to Post‐prandial Triglyceride‐enrichment of HDL Particles in Association with Endothelial and HDL Dysfunction - Verwer, Bart J. (Liver Int, 2020)
NAFLD is closely related with the metabolic syndrome (MetS) and increased risk of cardiovascular disease. Liver fat associates with post‐prandial hypertriglyceridemia, potentially contributing to triglyceride‐enrichment of high‐density lipoproteins (HDL‐TG), and subsequent HDL dysfunction. We assessed liver fat by MR spectroscopy, and its association with HDL physiochemical properties, and endothelial function, measured as flow‐mediated dilation (FMD), before and following three consecutive meals, in 36 men with type 2 diabetes mellitus (T2DM), with the MetS, and controls. Plasma triglycerides increased significantly following the meals (P < .001). Fasting HDL‐TG was highest in T2DM, relative to MetS and controls (P = .002), and increased post‐prandially in all groups (P < .001). HDL function was negatively associated with HDL‐TG following three meals (r = −.32, P<.05). Liver fat associated with HDL‐TG after three meals (r = .65, P < .001). HDL‐TG was independently associated with FMD following three consecutive meals (r = −.477, P = .003). We conclude liver fat is associated with post‐prandial HDL‐TG enrichment which was closely related with endothelial and HDL dysfunction.